2020
DOI: 10.1111/pace.14071
|View full text |Cite
|
Sign up to set email alerts
|

The ligament of Marshall and arrhythmias: A review

Abstract: The ligament of Marshall (LOM) is a remnant of the embryonic sinus venosus and left cardinal vein, and contains fat and fibrous tissues, blood vessels, muscle bundles, nerve fibers, and ganglia. The complexity of LOM's structure makes it as a source of triggers and drivers as well as substrates of re‐entry for atrial arrhythmias, especially for atrial fibrillation (AF). LOM also serves as a portion of left atrial macro‐re‐entrant circuit, especially peri‐mitral isthmus re‐entrant circuit. Experimental studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The vein of Marshall (VOM), which obliquely connects the posterolateral wall of left atrial and proximal coronary sinus, is one of the significant components inside the ligament of Marshall (LOM), which is accompanied by multiple structures, including fibrous tissue, blood vessels, muscle bundles, ganglion cells, and autonomic nerves (23). Accumulating studies had revealed that VOM was significantly associated with arrhythmias, and the potential pathophysiology mechanisms between the VOM and atrial arrythmia had been demonstrated, mainly including VOMrelated AT, VOM-related reentrant activities triggering AF, focal activities perpetuating AF, and unbalanced autonomic nervous system in proximal VOM (3). Preliminary clinical researches had reported that ethanol effusion into VOM showed an intriguing effect with inducing a complete linear lesion along the MI and achieving successful MI block (4,5), which made it a promising therapeutic approach for peri-mitral AT or post-AF AT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vein of Marshall (VOM), which obliquely connects the posterolateral wall of left atrial and proximal coronary sinus, is one of the significant components inside the ligament of Marshall (LOM), which is accompanied by multiple structures, including fibrous tissue, blood vessels, muscle bundles, ganglion cells, and autonomic nerves (23). Accumulating studies had revealed that VOM was significantly associated with arrhythmias, and the potential pathophysiology mechanisms between the VOM and atrial arrythmia had been demonstrated, mainly including VOMrelated AT, VOM-related reentrant activities triggering AF, focal activities perpetuating AF, and unbalanced autonomic nervous system in proximal VOM (3). Preliminary clinical researches had reported that ethanol effusion into VOM showed an intriguing effect with inducing a complete linear lesion along the MI and achieving successful MI block (4,5), which made it a promising therapeutic approach for peri-mitral AT or post-AF AT.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies had revealed that the vein of Marshall (VOM) was significantly associated with multiple arrhythmias (e.g., atrial arrhythmias, ventricular arrhythmias, and accessory pathways) (3). Meanwhile, preliminary studies indicated VOM as a promising therapeutic target for AF or post-AF AT.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, EIVOM can effectively affect these epicardial connections and exert a potent intervention to the myocardial AF substrate along the distribution of MB. In addition, EIVOM can eliminate triggering activation of VOM and lead to LA denervation 20 …”
Section: Discussionmentioning
confidence: 99%
“…The LOM may play an important role in the pathophysiology of various tachyarrhythmias, including ventricular tachycardias, atrioventricular re-entrant tachycardias, ridge-related perimitral atrial flutters, and atrial fibrillation (AF) ( 11 18 ). In patients with AF, the LOM may serve as either a source of triggered ectopic activity ( 8 , 14 , 19 ) or as an arrhythmogenic substrate ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%